Effects of heat input on arc stability and weld quality in underwater wet flux-cored arc welding of E40 steel. (January 2018) - Li, HongLiang; Liu, Duo; Yan, YaoTian; Guo, Ning; Liu, YiBo; Feng, JiCai
Abstract: Real-time electric signal data, microstructure characteristics and mechanical properties at six different heat inputs (16 kJ/cm ∼39 kJ/cm) in underwater wet flux-cored arc welding (FCAW) of E40 steel were investigated. The electric signal results showed that the arc stability would deteriorate at high heat input because of the formation of spatters. The heat input changed the chemical composition of weld metal. With increase in the heat input, the ultimate tensile strength and impact toughness of weld metal increased due to solid solution strengthening of alloying elements. Moderate heat input (22 kJ/cm and 25 kJ/cm) was optimum, good arc stability was obtained and mechanical properties was excellent. The heat input had limited effect on the hardness of CGHAZ although the cooling rate slowed down.